2012
DOI: 10.4293/108680812x13291597716663
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis of Portal Venous System after Laparoscopic Cholecystectomy in a Patient with Prothrombin Gene Mutation

Abstract: This analysis suggests that prothrombin gene mutation G20210A should be studied in the workup of intraabdominal venous thrombosis following laparoscopic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 4 publications
(5 reference statements)
0
16
0
1
Order By: Relevance
“…Local causes are abdominal inflammatory conditions such as pancreatitis, inflammatory bowel disease, infection, and abdominal surgeries especially with handling of the portal and mesenteric veins such as splenectomy [ 2 ]. Systemic causes are prothrombotic states secondary to genetic coagulopathies like protein C and S deficiency, prothrombin gene mutation [ 3 ], antithrombin III deficiency, factor V Leiden mutation, and hyperhomocysteinemia or acquired causes like contraceptive use [ 4 ], recent pregnancy, antiphospholipid syndrome, myeloproliferative disorders, and paroxysmal nocturnal hemoglobinuria.…”
Section: Discussionmentioning
confidence: 99%
“…Local causes are abdominal inflammatory conditions such as pancreatitis, inflammatory bowel disease, infection, and abdominal surgeries especially with handling of the portal and mesenteric veins such as splenectomy [ 2 ]. Systemic causes are prothrombotic states secondary to genetic coagulopathies like protein C and S deficiency, prothrombin gene mutation [ 3 ], antithrombin III deficiency, factor V Leiden mutation, and hyperhomocysteinemia or acquired causes like contraceptive use [ 4 ], recent pregnancy, antiphospholipid syndrome, myeloproliferative disorders, and paroxysmal nocturnal hemoglobinuria.…”
Section: Discussionmentioning
confidence: 99%
“…Preventza et al 6 reported a case of PMT associated with an elevation of the immunoglobulin G anticardiolipin antibody. Gul et al 4 reported about a patient with a heterozygous form of factor II (prothrombin) G20210A mutation. An exotic case of dengue viral infection-associated PMT after LCE was described by Dan et al 1 Dengue viral infection may be responsible for the downregulation of thrombomodulin-thrombin-protein C complex formation reducing activated protein C, activating the link between coagulation-inflammation pathways or autoimmunity against endothelial cells, but the most probable correlation between infection and thrombosis was dehydration as a major risk factor of thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…2,7 It is widely accepted that increased intra-abdominal pressure due to pneumoperitoneum can trigger PMT. 4 Several experimental and clinical studies showed that hepatic microcirculation, portal venous blood flow, and renal blood flow are decreased with increasing intra-abdominal pressure. 6,10 -13 Increased intra-abdominal pressure leads to a decrease in mesenteric and portal venous blood flow via direct pressure-induced compression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Системными причинами заболевания могут быть различные тромбофилические состояния и коагулопатии: дефицит протеинов S и C, генетические дефекты протромбина, лейденовская мутация, дефицит антитромбина III, гипергомоцистеинемия, мутация G20210 протромбина и мутация JAK2 V617F, а также различные системные предрасполагающие состояния (сепсис, беременность, использование оральных контрацептивов, миелопролиферативные заболевания) [13,20,28,34,40,41,70,84].…”
Section: этиологияunclassified